Persepsi Generasi Muda Dalam Konten Influencer Di Platform Media Sosial Tiktok (Studi Kualitatif Deskriptif Pada Akun @Dokterdetektif) - Syifa Muthmainah; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The lack of knowledge of the younger generation regarding the content of skincare products that are currently circulating on the TikTok platform has led to the abuse of skincare products that are not in accordance with their skin needs. Doctor Detectife provides education about dangerous skincare products and also overclaims through the TikTok account @dokterdetektif. The purpose of this research is to find out the perception and views of the younger generation towards the content presented by influencers on TikTok @dokterdetektif accounts. The research method used in this study is a qualitative study with a type of descriptive approach. The data was used by observation methods, in-depth interviews, and documentation. Data analysis uses data reduction, data presentation and conclusion drawn. The theory used in this study is the Uses and Gratifications (U&G) theory. The results of this study show that the perception of the younger generation towards skincare education content on the @dokterdetektif tiktok account is that the content can provide knowledge to the younger generation not to be easily tempted and carelessly use skincare products that contain harmful ingredients, where now there are many skincare products which gives excessive claims to its products, with this educational content making the younger generation more careful in choosing safe skincare products. The uniqueness of the results of this study highlights how the content not only provides information, but also equips the younger generation with critical knowledge not to be easily tempted by excessive claims from potentially harmful skincare products. With an approach that combines educational aspects and risk awareness, this study provides new insights into the importance of the role of social media in increasing the caution and selectivity of the younger generation in choosing beauty products, thereby contributing to better skin health.